Homozygous Pro74 → Arg Mutation in the Platelet Glycoprotein Ibβ Gene Associated with Bernard-Soulier Syndrome - Kunishima, Shinji; Tomiyama, Yoshiaki; Honda, Shigenori; Fukunishi, Mariko; Hara, Junichi; Inoue, Chikako; Kamiya, Tadashi; Saito, Hidehiko (Thrombosis and Haemostasis, 2000)
Bernard-Soulier syndrome (BSS) is an autosomal recessive bleeding disorder due to quantitative or qualitative abnormalities in the glycoprotein (GP) Ib/IX/V complex, the platelet receptor for von Willebrand factor. This complex is composed of four subunits, GPIbα, GPIbβ, GPIX and GPV. We describe here the genetic basis of the disorder in a patient with BSS. Flow cytometric analysis of the patient’s platelets showed greatly reduced GPIbα and GPIX surface expression. Immunoblot analysis disclosed absence of GPIbα, GPIbβ and GPIX in the platelets. DNA sequencing analysis revealed a novel missense mutation in the GPIbβ gene that converts Pro (CCG) to Arg (CGG) at residue 74. Homozygosity of the mutation was confirmed by allele-specific restriction analysis, chromosome 22 microsatellite analysis and quantitative Southern blotting. The mutant GPIbβ was normally transcribed. Transient transfection studies confirmed that mutant GPIbβ impairs surface expression of GPIb/IX, showing that the mutation is responsible for a BSS phenotype observed in the patient.
Keywords: Bernard-Soulier syndrome; chromosome 22; giant platelets; glycoprotein Ibβ; thrombocytopenia